Delayed collection of unemployment insurance in recessions - Zoe Xie (Federal Reserve Bank of Atlanta, 2019)
Using variations in unemployment insurance policies over time and across U.S. states, this paper provides evidence that allowing unemployed workers to delay the collection of benefits increases their job-finding rate. In a model with discrete job take-up decisions, benefit entitlement, wage-indexed benefits, and heterogeneous job types, I demonstrate that the policy can increase an unemployed worker's willingness to work, even though more benefits in general reduce the relative value of employment. In a calibrated quantitative model, I find that allowing delayed benefit collection increases the overall job finding rates and may lower the unemployment rate both in a steady state stationary economy and over a transition path during 2008−12.
Keywords: E24; J65; 330; unemployment insurance; social program design; Great Recession